2006
DOI: 10.1016/j.brat.2005.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anxiety on sexual arousal in women

Abstract: This study examined the impact of state anxiety, trait anxiety, and anxiety sensitivity on physiological and self-report measures of sexual arousal and sexual function in a non-clinical sample of women. Physiological sexual responses to an erotic stimulus were assessed using vaginal photoplethysmography, and subjective reactions were measured using questionnaires. Results suggested a curvilinear relationship between state anxiety and physiological sexual arousal (vaginal pulse amplitude; VPA). Trait anxiety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 43 publications
11
86
0
5
Order By: Relevance
“…This mechanism could serve to maintain and even intensify unwanted genital responding. The role of the enhanced sympathetic nervous system activity (Meston & Gorzalka, 1996) due to state anxiety (Bradford & Meston, 2006) in augmenting female genital responding has been shown in recent laboratory studies, and observed clinically for many years (Seto, 1992).…”
Section: Relevance To Psas?mentioning
confidence: 96%
“…This mechanism could serve to maintain and even intensify unwanted genital responding. The role of the enhanced sympathetic nervous system activity (Meston & Gorzalka, 1996) due to state anxiety (Bradford & Meston, 2006) in augmenting female genital responding has been shown in recent laboratory studies, and observed clinically for many years (Seto, 1992).…”
Section: Relevance To Psas?mentioning
confidence: 96%
“…In other words, greater negative affect is associated with greater, rather than lesser, sexual response in these studies. Others have proposed a curvilinear relationship between negative affect and genital response (Bradford & Meston, 2006;Seto, 1992) whereby intermediate levels of anxiety are associated with increased genital response, and high or low levels are associated with lower genital response. In other research, the experience of anger and irritability has been associated with reduced subjective and physiological sexual response (ter Kuile, Vigeveno, & Laan, 2007).…”
Section: Stimulus Intensitymentioning
confidence: 98%
“…Studies that focused on different types of negative affect reported a positive association between disgust and physiological sexual arousal (Heiman, 1980) and also a positive associationbetweenanxietyandbothgenitalandsubjectivesexualresponses (Beggs, Calhoun, & Wolshik, 1987;Elliott & O'Donohue, 1997;Hoon, Wincze, & Hoon, 1977;Laan, Everaerd, VanAanhold, & Rebel, 1993;Palace & Gorzalka, 1990). In addition, one study found a curvilinear relation between anxiety and genital arousal (Bradford & Meston, 2006), while others found no significant negative association between anxiety and sexual arousal (e.g., Heiman, 1980).…”
Section: Introductionmentioning
confidence: 94%